Barriers and levers to using an app for motor function assessment by therapists in hospitals: A qualitative study of the MFM-Play app - Dominique Vincent-Genod; Manon Verroul; Pascal Rippert; Shotaro Tachibana; Carole Vuillerot (PLoS ONE, 2026)
Background The Motor Function Measure (MFM) is an important evaluation tool used to monitor the progression of most neuromuscular diseases. However, the MFM is subject to inter-rater variability, and patients must produce their best effort, which can be difficult for children. In response to these issues, we developed a digital app named MFM-Play, designed to optimise completion of the MFM in a fun manner. The objective of this study was to explore barriers and levers to the MFM-Play’s use by therapists. Method We conducted a qualitative study with rehabilitation professionals who had tested the app in a previous reliability study. Individual interviews based on the Technology Acceptance Model were followed by a focus group based on the interview results. Thematic analysis was performed on transcripts. Results Seven therapists participated in the interviews and seven others in the focus group. The results revealed the multi-dimensional features related to adopting the MFM-Play app. Barriers related to ease of use, training and organisational constraints were identified, and were partly due to the additional mental burden of learning to use the technology. However, therapists who were at ease with the digital tool found it useful for their practice. The app also modified patient-therapist dynamics, fostering greater patient autonomy, but sometimes disrupted therapists’ habits, by calling into question assessment methods. Conclusion The MFM-Play app offers considerable practical and efficiency benefits; however, its successful adoption depends on overcoming technical, organisational, and user-specific barriers. This involves providing support for the change in the therapist’s stance within the triadic patient-therapist-tablet relationship.